Trichoderma spp. dan Penicillium spp. dari Tanah Rizosfer Lahan Rawa Lebak dalam Menginduksi Ketahanan Tanaman Cabai Terhadap Serangan Penyakit Rebah Kecambah - Ahmad Muslim; Syahri Syahri; Harman Hamidson; Abdullah Salim (Jurnal Fitopatologi Indonesia, 2014)
Soil microbes associated with rhizosphere are important for promoting plant growth and inducing resistance to diseases. The research was conducted to study the ability of Trichoderma spp. and Penicillium spp. isolated from rhizosphere in lowland swampy area for controlling damping-off disease caused by Rhizoctonia solani Khun. Trichoderma spp. and Penicillium spp. were cultured in bran, corn meal, and rice straw containing media and applied as inoculum to 2-weeks old seedlings. Application of two fungi isolates effectively induced resistance of chili plants to damping-off disease. Trichoderma spp. and Penicillium spp. were significantly reduced disease incidence by 61.5–100% to 46.2–100%, respectively and disease severity by 50–100% and 30–95.9%, respectively. This experiment showed the potential of Trichoderma spp. and Penicillium spp. as biocontrol agents to control damping-off disease on chili.